Principles of sustainable living a new vision for health, happiness, and prosperity - Jurin, Richard R. (Richard Robert) 1953- (Champaign, IL Human Kinetics, 2012)
No one can argue against wanting a better quality of life--and Principles of Sustainable Living: A New Vision for Health, Happiness, and Prosperity provides keen insight into how to achieve that so that individuals, communities, and the environment all come out winners. This transdisciplinary text presents principles of sustainability, develops environmental literacy, and expands awareness of sustainable practices that will steer readers toward a lifestyle that they, as well as the entire planet, will benefit from. Author Richard Jurin, an expert in sustainable living, has written numerous publications on sustainable development, business leadership for sustainability, and related issues. He takes students beyond sustainability's traditional "triple bottom line" of people, profit, and planet to a quadruple paradigm that includes economic, sociocultural, psychological, and ecological aspects of sustainability. The text offers: principles of sustainability that support a range of university courses in multiple disciplines; a systems approach to sustainability that reflects worldwide views and values; case studies, personal reflections, and applications that help students understand their status and the challenges of the future; and guidelines for developing sustainable living through daily choices. The book explores the mind-sets that have created the modern, consumer-based world we live in, exposing environmental and societal global problems as it does; lays out new ways of thinking, championing sustainable thinking as a prerequisite for living a healthy, happy, vibrant life that benefits the planet; and details positive options for living a sustainable lifestyle. Readers will be able to understand sustainability from a broad perspective--how it can improve their lives, resolve environmental problems, and improve the condition of the planet for all life. Principles of Sustainable Living points out the problems and challenges we face individually and as caretakers of our planet and offers lifestyle approaches that can sustain quality of life long into the future.
Chapter 1. Moving Toward a New Way of Living ; Attaining Sustainability ; Understanding What Is Important ; Worldviews That Shaped Our Thinking ; Barriers to Change ; Changing Our Thinking ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 2. Social and Cultural Trends ; Trends That Shape Our Lives ; Consequences of Current Trends ; Catalysts for Future Trends ; Creating New Trends ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 3. Standard of Living versus Quality of Life ; Waking Up From the Illusion of the American Dream ; Redefining Progress ; All-Encompassing Consumerism ; Advertising ; Marketing ; Adjusting Our Attitude ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 4. Thinking Systemically and Sustainably ; Systemic Versus Symptomatic Thinking ; Critical Thinking ; Analyzing Root Problems ; Thinking Sustainably ; Barriers to Changing our thinking ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 5. Economics, Prosperity, and Sustainability ; Brief History of Economics ; Types of Economies ; Our Current High Standard of Living ; Measures of Current Wealth ; Economics Undermining Community ; Managing and Avoiding Personal Debt ; Improving Economic Practices to Enhance Quality of Life ; New Measures of Prosperity ; Reshaping the Global Economy ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 6. Choosing a Healthy, Sustainable Lifestyle ; Reasons for Poor Health ; Industrial Farming ; Sustainable Farming Methods ; Corporate Agriculture versus Community Supported Agriculture ; Healthy Lifestyle Choices ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 7. Happiness and Well-Being ; Determinants of Happiness and Well-Being ; Ranking Happiness and Well-Being ; Emotional Well-Being ; Social Well-Being ; Ecological and Spiritual Well-Being ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 8. Education ; Education in the 21st Century ; Becoming an Informed Citizen ; Communicating Effectively ; Reforming Education ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 9. Technology and Industrial Ecology ; Shifting Toward a Sustainability Paradigm ; Technology Involves Risk ; Industrial Ecology ; Green Energy and Society ; Biommicry ; The Future of Electrical Energy ; Managing and Eliminating Waste ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 10. Community ; Types of Communities ; What Makes Up a Community ; Community Resilience ; Social Benefits of Community ; Substitute Communities ; Urban Renewal ; Postmodern Communities ; Economic Community ; Urban and Community Gardens ; Civic Agency ; Moving Toward Sustainable Communities ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 11. Transitioning to Sustainable Living ; Transitional Communities ; Ecovillages ; Relocalization and Resilience ; New Urbanism ; Summary ; Learning Activities ; Glossary ; References and Resources -- Chapter 12. On the Edge of Change ; Change Is Possible ; Transitioning to a New Culture ; Cultivating New Perspectives ; Adopting New Ideas ; Becoming Cultural Critics ; Facilitating Discussion ; Affecting Change ; Improving Policy-Making ; Creating a Cooperative World ; Achieving Empowerment ; Summary ; Learning Activities ; Glossary ; References and Resources.
Includes bibliographical references
Keywords: Sustainable living